BIM-based energy analysis and sustainability assessment - application to Portuguese buildings - Carvalho, José Pedro Almeida (2021)
Buildings are responsible for several negative impacts on the environment, most of them related to nonrenewable energy consumption, increasing the concern regarding buildings energy efficiency. In this context, computer software has been used to estimate the energy needs of the built environment, and the Building Information Modelling (BIM) methodology can be used to simplify this process. This study aims to validate a BIM-based framework to streamline the energy analysis of Portuguese buildings, based on the method of the national regulation for the thermal performance of residential buildings. Currently, designers need to spend considerable time assessing all the building characteristics and performing the mandatory calculations for energy performance analysis. It is also intended to link the results of the energy simulation with a Building Sustainability Assessment method—SBToolPT-H. The purpose is to demonstrate how it is possible to benefit from this approach to simultaneously improve building sustainability during the design stage. To do so, different case studies were modelled in Autodesk Revit and exported to a BIM energy tool to perform energy simulation analysis. The results were validated against the official assessment method of the Portuguese thermal regulation and were successfully used to assess the SBToolPT-H energy efficiency category. The research outcomes provide design teams with a reliable BIM-based framework to improve building energy performance and to develop thermal projects while enhancing building sustainability. It also increases the knowledge about the integration of sustainability assessment in the BIM environment, providing new insights for complete integration.